O ADMINISTRADOR DE ESCOLA BÁSICA NO EIXO DAS RELAÇÕES HISTÓRICO-SÓCIO-CULTURAIS: A PRODUÇÃO DE SUBJETIVIDADES - Nunes, Elizabete Kuczynski (Revista Liberato, 2013)
The present work is situated in the research field of School and Educational Policies in Multicultural Society and it has the general goal of discussing the Basic School administrator’s personal trajectory and his/her processes of identification with the administrative practice. In order to know and understand how the production of subjectivities in the relations of action and interaction of the school administrator happens in the school itself, aspects of his familiar, academic and professional background are analyzed. This research is based on the true lives of two Modern Foreign Languages teachers from two public schools of the state of Rio Grande do Sul, who changed over from the pedagogical to the administrative practice.